The Reuse of Recyclable Materials in the Construction of Educational Eco-Toys for Early Childhood (Research, Society and Development, 2022)
Education is the basis of ecological awareness, thus, it is possible to guide practical questions regarding environmental awareness considering early childhood, as this is a period of significant learning. This work seeks to stimulate ecological awareness considering the playfulness and reuse of materials in the construction of eco-toys aimed at children in early childhood in a situation of social or educational vulnerability, with the objective of investigating the inclusion of Environmental Education practices in everyday life. as a strategy to understand the change in behavior and attitudes in children aged 0 to 3 years at social risk. Aiming at the environmental context within this relationship between child and caregiver, about 30 children were monitored weekly by the Happy Child Program in the city of Araripe-CE. To monitor the children's development, the act of playing was observed weekly. It is a fact that the act of playing awakens the imagination of children. When placed in front of reusable material with the challenge of transforming them, they find ways to use these items in their play. In order to assess and monitor child development, the children who participated in the research showed a satisfactory result, even though it was a partial result, the study showed that children who play develop better. With regard to playing, inserting toys with recycled materials makes it possible for the child to become aware of the preservation of the Environment through play.